(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Elena-Andreea Bărbulescu analyzes the symbolic importance of reading in George Orwell’s 1984 and Ray Bradbury’s Fahrenheit 451. The study explores how reading shapes individual identity against totalitarian regimes. In 1984, reading acts as a deceptive trap through "doublethink," leading to Winston’s destruction. Conversely, Fahrenheit 451 presents reading as a hopeful, transformative force, where individuals become "living libraries." Ultimately, the author contrasts Winston’s passive failure with Montag’s active rebellion and spiritual rebirth. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.